Adobe Photoshop elements 7 on demand - Johnson, Steve, 1961- (Que, 2009)
Adobe Photoshop Elements 7 on Demand What you need, when you need it! Need answers quickly? Adobe Photoshop Elements 7 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Inside the Book " Browse, organize, and process files using the Organizer " Easily find and vie w just the photos and video clips you want to see " Whiten teeth, deepen a blue sky, and more with a single click using the new Smart Brush " Use auto controls to quickly fix a photo " Use Guided Edit to walk you step by step through the editing process " Use more precise color correction to enhance a photo " Easily brush away wrinkles and other unwanted photo results " Use image trickery and special effects to change or enhance a photo " Use themes and artwork to liven up your photo projects " Create perfect group shots, seamless panoramas, tourist-less landscapes, and more Bonus Online Content Register your book at queondemand.com to gain access to: " Workshops and related files " Keyboard shortcuts Visit the author site: perspection.com